-25, -21, -17, -13, -9, -5, -1, 3, 7, 11, 15
The pattern is that it increases by 4,
or if y = 9x - 5(x-3) - 20
y(n) = y(n-1) + 4 where n represents the position of each number is the original sequence -5, -4, ... , 4, 5
2007-05-21 17:31:50
·
answer #1
·
answered by Kinger 2
·
0⤊
0⤋
Just plug x=-5,-4,-3,-2,-1,0,1,2,3,4,5
into the equation!
For example: When x=1. the expression becomes: (9*1) - 5(1-3) - 20 = 9 +10 - 20 = -1
The solutions are:
When x = -5, the expression yields: -25
When x = -4, the expression yields: -21
When x = -3, the expression yields: -17
When x = -2, the expression yields: -13
When x = -1, the expression yields: -9
When x = 0, the expression yields: -5
When x = 1, the expression yields: -1
When x = 2, the expression yields: 3
When x = 3, the expression yields: 7
When x = 4, the expression yields: 11
When x = 5, the expression yields: 15
2007-05-22 00:20:27
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
Yes, there is. Just 'plug in' the numerical value given in place of x, do the indicated arithmetic, and you're done. First one
9*(-5) -5*((-5)-3)-20 = -25 And you do the rest âº
Doug
2007-05-22 00:22:35
·
answer #3
·
answered by doug_donaghue 7
·
0⤊
0⤋
Should be. Simplify your expression to 4x-5 This would indiciate that at x=0, the expression will be
-5, and for each increase in x of 1, the expression will increase 4.
2007-05-22 00:22:08
·
answer #4
·
answered by cattbarf 7
·
1⤊
1⤋
9x-5(x-3)-20
9x-5x+15-20
4x-5
4x-5
-20-5
-25
4x-5
-16-5
-21
4x-5
-12-5
-17
4x-5
-8-5
-13
4x-5
-4-5
-9
4x-5
0-5
-5
4x-5
4-5
-1
4x-5
8-5
3
4x-5
12-5
7
4x-5
16-5
11
4x-5
20-5
15
Add 4
2007-05-22 00:24:23
·
answer #5
·
answered by amethyst_fire_lily 2
·
0⤊
0⤋